Building on Academic Culture of Campus: Comparison of Individual Behavior of Ma’had Students and Boarding Houses of IAIN Lhokseumawe - Jannah, Miftahul; Firdaus, Muammar (Islamic Educational Management Programme, 2022)
This study aims to find out and analyze how to build an academic culture outside the campus, namely at the Ma'had Jami'ah College of Institut Agama Islam Negeri Lhokseumawe. The research method used is a qualitative descriptive survey technique. The sources of informants in this study were ma'had leaders and students majoring in Islamic Education Management who live in ma'had. The results showed that as many as 48 students of Islamic education management who only lived in ma'had were only 3 students, the rest preferred to stay in boarding houses or depart from home even though the distance traveled sometimes exceeded one hour. Meanwhile, from ma'had the distance to the faculty is very close. Many of those who do not live in ma'had or have ever been in ma'had assume that they are not used to living in an orderly or disciplined atmosphere. As life has been lived by students who have settled in ma'had.